Design of a Ribāṭ-Based Module Adaptation Model to Strengthen Learners’ Resilience at PKBM Alam Jingga - Febi Robianti; Herlin Kusumasari; Dilla Nurbait Sholeh (Jurnal Pendidikan Non formal, 2025)
This study conceptualizes a Ribāṭ-based resilience learning module for Indonesian Islamic education, targeting Fase D (middle school) students at PKBM Alam Jingga. Using a qualitative document-based adaptation method with narrative synthesis, thematic analysis, and Interpretative Phenomenological Analysis (IPA), the study integrated classical Islamic ethical principles with contemporary resilience frameworks. The UCLG Resilience Learning Module I served as the reference for adaptation. Key Ribāṭ principles—moral vigilance (murāqabah), spiritual perseverance (ṣabr), structured routines, self-discipline, and community responsibility—were operationalized through four components: Ribāṭ Awareness, Ribāṭ Disciplinary Practices, Ribāṭ Resilience Competencies, and Ribāṭ Community Engagement. The model fosters psychological, moral, and social resilience via reflective exercises, scenario-based problem solving, and community projects. Findings suggest that Ribāṭ principles enhance ethical reasoning, emotional regulation, spiritual fortitude, and collective responsibility, offering a holistic approach to youth development.